2021
DOI: 10.1039/d1ra03362j
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the degradation mechanism of LaCoO3-based symmetric supercapacitors

Abstract: Cycling tests for LaCoO3-based symmetric supercapacitors were carried out. The change in the valence state of Co in the electrode surface active material, LaCoO3, before and after the cycling test was investigated by X-ray photoelectron spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…By considering the results obtained from the CV curves, optical absorption, Raman and XPS, we infer that redox reactions are the main charge storage mechanism of the SLG/LSC‐SC device and the redox centers are the oxygen vacancies as well as the Co 3+ /Co 2+ species. Finally, we should mention that the continuous charging/discharging cycles decreases the amount of the Co 2+ species in the electrodes and the Co 3+ species become more abundant, this in turn, reduces the content of oxygen vacancies and makes the redox reactions less efficient for the charge storage [54] . For this last cause, the capacitance retention is lower at the end of 500 charge/discharge cycles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By considering the results obtained from the CV curves, optical absorption, Raman and XPS, we infer that redox reactions are the main charge storage mechanism of the SLG/LSC‐SC device and the redox centers are the oxygen vacancies as well as the Co 3+ /Co 2+ species. Finally, we should mention that the continuous charging/discharging cycles decreases the amount of the Co 2+ species in the electrodes and the Co 3+ species become more abundant, this in turn, reduces the content of oxygen vacancies and makes the redox reactions less efficient for the charge storage [54] . For this last cause, the capacitance retention is lower at the end of 500 charge/discharge cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we should mention that the continuous charging/discharging cycles decreases the amount of the Co 2 + species in the electrodes and the Co 3 + species become more abundant, this in turn, reduces the content of oxygen vacancies and makes the redox reactions less efficient for the charge storage. [54] For this last cause, the capacitance retention is lower at the end of 500 charge/ discharge cycles.…”
Section: Chemistryselectmentioning
confidence: 99%
“…The variation in η c and C ret observed in this study was similar to the trend reported previously. 61 Galvanostatic charge− discharge assays were also performed applying a lower constant current of 0.06 A cm −3 . Under this low current and after 62 h/ 1000 cycles of galvanostatic charge−discharge within a 2 V potential window, the total initial time of the charge−discharge obtained was 146 s (Figure S5, Supporting Information); LEA = 6.49%, C ret = 93.5% and η c = 100%.…”
Section: Resultsmentioning
confidence: 99%
“…The marginal variation observed in η c and C ret can be attributed to a combination of multiple factors such as (i) slight change in the ambient temperature during measurements, (ii) volume changes affecting the electrode surface roughness during the charge–discharge measurements, consequently impacting the contact area between the electrode and the electrolyte, and (iii) intense polarization of the electrodes at a high applied potential (2 V) used in this work, which could affect reversibility and stability of ionic charges. The variation in η c and C ret observed in this study was similar to the trend reported previously . Galvanostatic charge–discharge assays were also performed applying a lower constant current of 0.06 A cm –3 .…”
Section: Resultsmentioning
confidence: 99%
“…5 Measurement of "equivalent series resistance (ESR)," along with capacitance, is a general way to observe and predict the "end of life (EoL)" 6 of super capacitors. The degradation mechanism, which eventually corresponds to EoL, 7 mainly depends on the changes occurred in active surface area of electrodes, 8,9 in association with formation of gaseous products as outcome of electrolyte degradations, followed by saltprecipitations. 10,11 To account the degradation mechanism up to a significant extent, electrochemical impedance spectroscopy (EIS) is one of the most preferred methods.…”
Section: Introductionmentioning
confidence: 99%